MOTIVASI DALAM PENDIDIKAN - Nur Sri Putri Muis; Azwa Alif Alisa; A. Rahma Febriana; Idawati (STKIP Subang, 2026)
Learning motivation is a crucial factor influencing the success of the learning process. Students with high motivation tend to demonstrate persistence, active participation, and optimal learning outcomes. This paper aims to examine the concept of motivation in education, including the definition of learning motivation, motivational theories, types of intrinsic and extrinsic motivation, functions of motivation, and its role in the learning process. This study employs a literature review by analyzing theories from experts in psychology and education. The findings indicate that motivation functions as a driving force, a direction setter, and a reinforcement of students’ learning behavior. Teachers play a strategic role in fostering learning motivation by creating a supportive learning environment and applying appropriate instructional strategies.